Exploring Effectiveness Reserves in Hospitals with the DEA Method - Kucsma, Daniella; Varga, Krisztina (Public Finance Quarterly, 2021)
In our study, we undertake a relative efficiency analysis of hospitals providing inpatient care, which play a key role in the Hungarian health care system. According to the Competitiveness Report 2020 of the Hungarian National Bank, the Hungarian health care system has a number of reserves, and the sustainability of the system can be improved by using these reserves. In the 2015-2019 period, particular attention has been paid to the identification of achievable and meaningful indicators in the sector under review. The relative effectiveness analysis (DEA) method can be used to address this challenge. The units of our analysis are state-owned institutions in Hungary, typologised by the total number of beds. General profile hospitals with a bed count between 600 and 1200 beds were included in the analysis. The results of running the programme have clearly shown that there are some institutions that do not operate as efficiently as the majority of the organisations included in the study, but further research and refinement of the indicators is needed to determine the practical application of the pilot studies.